PSYCHOLOGICAL CHARACTERISTICS OF PRIMARY SCHOOL STUDENTS AND THEIR ADAPTABILITY TO SCHOOL EDUCATION - Abdullajonova Dilnozaxon Sultanbekovna; Jorayeva Dilfuza Abduganiyevna (Journals Park Publishing, 2022)
Psychological readiness for education means that the child meets the requirements of the school objectively and subjectively. He is psychologically prepared for school education, and therefore his psyche is sufficiently developed to acquire knowledge. , differs from children of other ages in the clarity of his thinking. In a child preparing for school, attention is relatively long-term and conditionally stable. Features of a child's attention include role-playing and storytelling, drawing and construction activities, making clay and plasticine toys, understanding and comprehending the speech of others, and solving mathematical problems.
Keywords: ethical norms; learning activities; learning tasks